2024
DOI: 10.5194/wes-9-359-2024
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid-Lambda: a low-specific-rating rotor concept for offshore wind turbines

Daniel Ribnitzky,
Frederik Berger,
Vlaho Petrović
et al.

Abstract: Abstract. We introduce an aerodynamic rotor concept for an offshore wind turbine which is tailored for an increased power feed-in at low wind speeds by a substantial increase in the rotor diameter while maintaining the rated power. The main objective of the conceptual design is to limit the steady-inflow loads (blade flapwise root bending moment (RBM) and thrust) to the maximum values of a reference turbine. The outer part of the blade (i.e. outer 30 % span) is designed for a higher design tip speed ratio (TSR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This enables the turbines to produce more power at lower wind speeds and also reach higher up in the atmosphere, where a higher energy availability is present. However, as shown in steady state blade element momentum simulations, the increase in power obtained from a single turbine only amounts to 11 % [3]. Thus, a second effect is assumed to contribute to the higher AEP.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This enables the turbines to produce more power at lower wind speeds and also reach higher up in the atmosphere, where a higher energy availability is present. However, as shown in steady state blade element momentum simulations, the increase in power obtained from a single turbine only amounts to 11 % [3]. Thus, a second effect is assumed to contribute to the higher AEP.…”
Section: Discussionmentioning
confidence: 93%
“…The investment cost (CAPEX) of these new turbine concepts will be higher compared to classical concepts, due to higher material costs, as the the tower is taller and the blades longer. However, previous studies suggested that the increased CAPEX may be balanced out by their increased value for the energy system as a whole, as this new concept is able to produce more power at lower wind speeds, when the demand is highest [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations